The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1177/000313481307900714
|View full text |Cite
|
Sign up to set email alerts
|

Associated Injuries in Traumatic Sternal Fractures: A Review of the National Trauma Data Bank

Abstract: Sternal fractures occur infrequently with blunt force trauma. The demographics and epidemiology of associated injuries have not been well characterized from a national trauma database. The National Trauma Data Bank was queried for patients with closed sternal fractures. The demographics were analyzed by age, gender, mechanism and indicators of anatomic and physiologic injuries. Types of commonly associated injuries were also determined. A total of 23,985 records were analyzed. Males accounted for 68.3 per cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
38
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 17 publications
8
38
0
1
Order By: Relevance
“…They were associated with rib fractures and hemothorax/hemopneumothorax. A most recent study [12] found similar results, with 3.6% of cardiac contusion, 16.9 % of lumbar fractures. In this study, mortality rate was 7.9%.…”
Section: Sternal Fracturessupporting
confidence: 61%
“…They were associated with rib fractures and hemothorax/hemopneumothorax. A most recent study [12] found similar results, with 3.6% of cardiac contusion, 16.9 % of lumbar fractures. In this study, mortality rate was 7.9%.…”
Section: Sternal Fracturessupporting
confidence: 61%
“…In trauma patients, additional variables, such as the ISS and the critical need for prehospital intubation, increase the risk of developing pneumonia [ 15 ]. Multiple previous studies have reported that trauma factors, such as pulmonary contusion, rib fracture, sternal fracture, and traumatic brain injury, increased the risk of developing pneumonia [ 4 , 5 , 16 , 17 ]. In the present study, the overall rate of VAP development was approximately 45.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Sternal fracture is a common injury often associated with fractures of vertebrae, most commonly thoracic [ 3 , 4 ]. Oyetunji et al [ 5 ] in an analysis of 23,985 trauma bank records in the USA reported 21.6% association with thoracic vertebra fracture and 16.9% with lumbar vertebra fractures. The overall mortality of sternal fractures is 0.7% but the mortality may increase to 10% in the presence of other associated injuries [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%